2003
DOI: 10.1136/jnnp.74.9.1206
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and causes of dementia in people under the age of 65 years

Abstract: Objectives: To determine the prevalence of dementia in people under the age of 65 in a large catchment area, and use these figures to estimate the number of younger people affected by dementia in the UK. Design: Epidemiological catchment area prevalence survey. Setting: The London boroughs of Kensington and Chelsea, Westminster, and Hillingdon with a total population of 567 500 people. Participants: All residents of the catchment area with dementia, where the illness began before the age of 65 years. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
503
7
43

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(574 citation statements)
references
References 16 publications
21
503
7
43
Order By: Relevance
“…The prevalence of presenile dementia is lower that ones with onset in the elderly. Harvey et al 4 reported that the prevalence increases exponentially between 45 to 60 years of age; this finding was replicated by another three epidemiological studies [5][6][7] . The most frequent diagnosis in early onset dementia is:…”
supporting
confidence: 69%
“…The prevalence of presenile dementia is lower that ones with onset in the elderly. Harvey et al 4 reported that the prevalence increases exponentially between 45 to 60 years of age; this finding was replicated by another three epidemiological studies [5][6][7] . The most frequent diagnosis in early onset dementia is:…”
supporting
confidence: 69%
“…The disease inflicts the person’s identity, threatens their self-image and self-confidence, and erodes plans for the future. Cognition will gradually decline among people with dementia (Harvey, Skelton-Robinson, & Rossor, 2003; Koedam et al, 2008; Luscombe, Brodaty, & Freeth, 1998), and the abilities to take care of daily activities and themselves, and to localize and move around on their own will deteriorate. The development of YOD and receiving the dementia diagnosis are reasonably followed by anxiety, turmoil, depression (Haugen, 2012; Johannessen & Möller, 2013), reduced quality of life and increased problems in everyday life in relation to work, friends and family (Spreadbury & Kipps, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Behaviour will change, and behavioural changes are more frequent in YOD than in people with late-onset dementia (LOD; van Vliet et al, 2012). Usually, people with YOD are diagnosed at a later stage of the disease compared to people with LOD (Harvey et al, 2003; Koedam et al, 2008; Luscombe et al, 1998). In Norway, studies indicate that about 50% of people with dementia who receive homecare services have not been diagnosed with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Increased severity of dementia has been linked to more NPS (such as agitation, aggression, and apathy) in NH residents with YOD and LOD (Mulders et al, 2016;Zuidema, de Jonghe, Verhey, & Koopmans, 2009). In addition, frontotemporal dementia (FTD) is more common in YOD; higher levels of agitation, disinhibition, and irritability are found in people with FTD than in those with AD, at least in the community-dwelling population (de Vugt et al, 2006;Harvey, Skeleton-Robinson, & Rossor, 2003;Mulders et al, 2014;Ratnavalli, Brayne, Dawson, & Hodges, 2002).…”
Section: Introductionmentioning
confidence: 99%